Experience capitalization: Wanted - a fertile soil for our seeds - Natha, Edson (Technical Centre for Agricultural and Rural Cooperation, 2019)
The planning process of a new capitalization exercise should start by looking in detail at the exercise we just completed. Now, if I am to reconstruct our participation in the experience capitalization workshop in Maputo, I have to start by saying that during the first few days it was very difficult to see what we were doing, or to see what we had to do.